"A class act: Constance Lytton and the political, literary and dramatic dynamics of suffrage prison writings". Issue 1 (2nd January 2019) - Eltis, Sos
ABSTRACT: In 1910 suffragette Lady Constance Lytton disguised herself as a working-class seamstress, Jane Warton. Her cross-class masquerade revealed the snobbery and injustice of prison authorities' treatment of suffragettes: as Lady Constance Lytton she was diagnosed with a weak heart and placed in the hospital wing, but as Jane Warton she was put in the Third Division and force-fed until her health gave out. Lytton's memoir, Prisons and Prisoners. Some personal experiences. By Constance Lytton and Jane Warton, Spinster became one of the most celebrated suffrage texts. This article reveals the literary and political sophistication of Lytton's writings, and argues that her innovative use of metaphor and her deployment of contemporary dramatic techniques and theories are crucial to appreciating the power and influence of her memoir. Drawing on contemporary feminist and suffrage theater and using the relation between actor and role as a framework for her account of her disguise and imprisonment, Lytton's memoir is both a skillful feminist negotiation of class tensions within the suffrage movement, and an example of how suffrage narratives can expand the extant canon of modernist writing.